Resource use efficiency of maize production with and without irrigation system in Kaski, Nepal - Khanal, Kapil; Adhikari, Kalika Bahadur; Dhakal, Shiva Chandra; Marahatta, Santosh (Journal of Agriculture and Natural Resources, 2020)
The study examined the resource use efficiency of maize production in rainfed and irrigated conditions in Kaski, Nepal. It focused specially on the production function of maize, resource use efficiency and socioeconomic characteristics of the farmers. A well-structured interview schedule was used in this study. Out of the 368 households interviewed, 165 farmers cultivated maize and a total of 157 farmers (59 from irrigated and 98 from rainfed) provided useful data. The data analysis was done by using Microsoft excel and SPSS. Cobb-Douglas production function was used to determine the resource use efficiency of maize production.  Compared to rainfed system, maize productivity in irrigated system was higher despite the use of fewer input implying irrigation. Increase in seed use by 10% increased the yield by 1.9% in case of rainfed system and 0.05% in case of the irrigated system. The major implication for the study is that farmers should make proper utilization of their resources to achieve higher level of resource use efficiency.